2024
DOI: 10.3390/cells13100853
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Myeloma: The Role of Autologous Stem Cell Transplantation in the Era of Immunotherapy

Serena Rocchi,
Beatrice Anna Zannetti,
Giovanni Marconi
et al.

Abstract: Upfront high-dose therapy with melphalan (HDM) followed by autologous stem cell transplantation (ASCT) has established itself as a core treatment for newly diagnosed multiple myeloma (NDMM) patients in the past 30 years. Induction therapy, HDM-ASCT, and subsequent consolidation and maintenance therapy comprise the current fundamental framework for MM treatment. The introduction of anti-CD38 monoclonal antibodies such as daratumumab and isatuximab has changed the treatment paradigm for transplant-eligible NDMM … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 93 publications
(100 reference statements)
0
1
0
Order By: Relevance
“…In the context of molecular biomarkers, Bergantim et al [ 6 ] demonstrated the feasibility of isolating and characterizing extracellular vesicles (EVs) obtained from multiple myeloma (MM) patients’ bone marrow and peripheral blood samples at diagnosis and remission. MM is an incurable disease and the third most common hematological neoplasia, accounting for 10% of newly diagnosed hematological neoplasia [ 7 ]. This neoplasia arises from the malignant transformation of post-germinal center plasma cells [ 8 ].…”
mentioning
confidence: 99%
“…In the context of molecular biomarkers, Bergantim et al [ 6 ] demonstrated the feasibility of isolating and characterizing extracellular vesicles (EVs) obtained from multiple myeloma (MM) patients’ bone marrow and peripheral blood samples at diagnosis and remission. MM is an incurable disease and the third most common hematological neoplasia, accounting for 10% of newly diagnosed hematological neoplasia [ 7 ]. This neoplasia arises from the malignant transformation of post-germinal center plasma cells [ 8 ].…”
mentioning
confidence: 99%